From Kisiizi to Baltimore: cultivating knowledge brokers to support global innovation for community engagement in healthcare - Ibe, Chidinma A; Basu, Lopa; Gooden, Rachel; Syed, Shamsuzzoha B; Dadwal, Viva; Bone, Lee R; Ephraim, Patti L; Weston, Christine M; Wu, Albert W; Barron, J.; Boonyasai, R. T; Gentry, J.; et al. (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Reverse Innovation has been endorsed as a vehicle for promoting bidirectional learning and information flow between low- and middle-income countries and high-income countries, with the aim of tackling common unmet needs. One such need, which traverses international boundaries, is the development of strategies to initiate and sustain community engagement in health care delivery systems. Objective In this commentary, we discuss the Baltimore “Community-based Organizations Neighborhood Network: Enhancing Capacity Together” Study. This randomized controlled trial evaluated whether or not a community engagement strategy, developed to address patient safety in low- and middle-income countries throughout sub-Saharan Africa, could be successfully applied to create and implement strategies that would link community-based organizations to a local health care system in Baltimore, a city in the United States. Specifically, we explore the trial’s activation of community knowledge brokers as the conduit through which community engagement, and innovation production, was achieved. Summary Cultivating community knowledge brokers holds promise as a vehicle for advancing global innovation in the context of health care delivery systems. As such, further efforts to discern the ways in which they may promote the development and dissemination of innovations in health care systems is warranted. Trial registration Trial Registration Number: NCT02222909 . Trial Register Name: Reverse Innovation and Patient Engagement to Improve Quality of Care and Patient Outcomes (CONNECT). Date of Trial’s Registration: August 22, 2014.